2016
DOI: 10.3390/risks4010007
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Time Series and Neural-Network Models of Exchange Rates between the US Dollar and Major Currencies

Abstract: Abstract:This paper features an analysis of major currency exchange rate movements in relation to the US dollar, as constituted in US dollar terms. Euro, British pound, Chinese yuan, and Japanese yen are modelled using a variety of non-linear models, including smooth transition regression models, logistic smooth transition regressions models, threshold autoregressive models, nonlinear autoregressive models, and additive nonlinear autoregressive models, plus Neural Network models. The models are evaluated on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…A consideration of the empirical studies has shown the effect of the fluctuation of exchange rates on exports, trade, investment, capital market, inflation, and employment growth-in developing and developed countries (Schnabl 2008;Jamil et al 2012;Rjoub 2012;Allen et al 2016;Alagidede and Ibrahim 2017;Dal Bianco and Loan 2017;Latief and Lefen 2018;Vo and Zhang 2019;Hatmanu et al 2020;Ioan et al 2020). However, the effect of exchange rate volatility on economic growth for CEE countries has been studied by few authors and there has been a lack of studies over recent years- (Ricardo et al 2007;Arratibel et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A consideration of the empirical studies has shown the effect of the fluctuation of exchange rates on exports, trade, investment, capital market, inflation, and employment growth-in developing and developed countries (Schnabl 2008;Jamil et al 2012;Rjoub 2012;Allen et al 2016;Alagidede and Ibrahim 2017;Dal Bianco and Loan 2017;Latief and Lefen 2018;Vo and Zhang 2019;Hatmanu et al 2020;Ioan et al 2020). However, the effect of exchange rate volatility on economic growth for CEE countries has been studied by few authors and there has been a lack of studies over recent years- (Ricardo et al 2007;Arratibel et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Boston and Firtescu (2019) also concluded that interest rates affect the financial markets and create a competitive environment. Different researchers have also studied that there is an effect of EMU on exchange rate on investment, exports, employment growth, capital markets, and inflation (Ioan et al, 2020;Dal Bianco & Loan, 2017;Schnabl, 2008;Allen et al, 2016;Latief & Lefen, 2018;Rjoub, 2012;Hatmanu et al, 2020;Jamil et al, 2012;Alagidede & Ibrahim, 2017;Vo & Zhang, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of all the methods and methodologies used in literature, three classes of models namely, stochastic models, Neural Network based models and Support Vector Regression based models were identified by [2] as the most popular ones for modelling financial time series. According to [3], [4], stochastic models such as random walk process and GARCH models could be used to represent time series. However, according to reference [5], GARCH models failed to capture the variations in the exchange rate series and concluded inefficient in forecasting exchange rates.…”
Section: Related Workmentioning
confidence: 99%